Methylpiperidinium Iodides as Novel Antagonists for α7 Nicotinic Acetylcholine Receptors - López, Jhon J.; García-Colunga, Jesús; Pérez, Edwin G.; Fierro, Angélica (Frontiers in Pharmacology, 2018)
The α7 nicotinic acetylcholine receptor (nAChR) is expressed in neuronal and non-neuronal cells and is involved in several physiopathological processes, and is thus an important drug target. We have designed and synthesized novel piperidine derivatives as α7 nAChR antagonists. Thus, we describe here a new series of 1-[2-(4-alkoxy-phenoxy-ethyl)]piperidines and 1-[2-(4-alkyloxy-phenoxy-ethyl]-1-methylpiperidinium iodides (compounds 11a-11c and 12a-12c), and their actions on α7 nAChRs. The pharmacological activity of these compounds was studied in rat CA1 hippocampal interneurons by using the whole-cell voltage-clamp technique. Inhibition of the choline-induced current was less for 11a-11c than for the methylpiperidinium iodides 12a-12c and depended on the length of the aliphatic chain. Those compounds showing strong effects were studied further using molecular docking and molecular dynamics simulations. The strongest and non-voltage dependent antagonism was shown by 12a, which could establish cation- interactions with the principal (+)-side and van der Waals interactions with the complementary (-)-side in the α7 nAChRs. Furthermore, compound 11a forms hydrogen bonds with residue Q115 of the complementary (-)-side through water molecules without forming cation- interactions. Our findings have led to the establishment of a new family of antagonists that interact with the agonist binding cavity of the α7 nAChR, which represent a promising new class of compounds for the treatment of pathologies where these receptors need to be negatively modulated, including neuropsychiatric disorders as well as different types of cancer.